A potentiometric study of the performance of a commercial copolymer in the precipitation of scale forming minerals. Issue 30 (30th June 2016) - Ruiz-Agudo, Cristina; Putnis, Christine V.; Ibañez-Velasco, Aurelia; Ruiz-Agudo, Encarnación; Putnis, Andrew
Abstract : The main effect of a commercial copolymer of maleic acid on CaCO3 and BaSO4 precipitation seems to be related to prevention of the aggregation of prenucleation associates and consequently inhibiting (temporarily) the nucleation of a secondary phase. Abstract : The mechanisms by which a commercial copolymer of maleic acid/allyl sulfonic acid with phosphonate groups (MASP), commonly used to mitigate or retard scale formation in the oil recovery industry, modifies the early precipitation stages of two common scale forming minerals, calcite and barite, have been investigated. MASP displays very similar effects on both CaCO3 and BaSO4 precipitation. The additive does not seem to significantly affect the equilibrium of pre-nucleation associates. Its main effect seems to be related to prevention of the aggregation of prenucleation associates and consequently inhibiting (temporarily) the nucleation of a secondary phase. MASP molecules hinder the aggregation of pre-nucleation ion associates by incomplete stabilization of such ion aggregates. When the amount of MASP cannot prevent prenucleation cluster aggregation, nucleation occurs at higher supersaturation via amorphous intermediates that later transform into crystalline phases. Finally, the growth of the crystal occurs through non-classical oriented aggregation of nanoparticles that seem to incorporate the copolymer that stabilizes them and prevents merging. Our results have implications for the rationalization of the selection and use of polymeric additives as scale inhibitors, and provide useful insights into the mechanisms by which large biomacromolecules, commonly containing acidic groups similar to those of the studied additive, control mineral formation.